Basic Tenets of Experiential Learning in Emergent Reading Activities in Early Childhood Development and Education Centres in Kenya: A Comparison of Public and Private Schools - Chepsiror, Philomena (International Journal of Social Sciences Perspectives, 2021)
Emergent reading competencies are building blocks for learning to read. To successfully acquire these competencies, leaners have to be supported to utilize their interest and talents through personalized or experiential learning. Kenya is currently implementing a Competency Based Curriculum (CBC) which aims to make learners active participants in the learning process. However recent studies have shown that teachers still tend to teach content as opposed to building competencies. The focus of this study was to assess if teaching activities in emergent reading instruction in Kenya conform to the basic tenets of experiential learning. The study utilized the survey research design. Data was collected from 102 Pre-Primary one (PP1) teachers in public and 34 in private pre-schools who were randomly selected from Bureti Sub-County in Kenya, using questionnaire and observation checklist. The study found that basic tenets of experiential learning are largely adhered to in the public pre-schools, while there is still a lot to be desired in the private schools. The study recommends that continuous retraining was necessary especially in the private entities as well as availing experts in the field to mentor teachers and model best practice in competency based education.